The Effect of Cognitive Empowerment on Working Memory and Observational Learning of a Motor Skill in Children - Maryam Kavyani; Behrouz Abdoli; Reza Ebrahimi (University of Tehran, 2020)
The main aim of this study was to investigate the effect of cognitive empowerment on working memory and observational learning of dart throwing skill in children. 40 students aged between 10 and 11 were selected by convenience sampling method. In the first phase, cognitive empowerment was performed and in the second phase observational learning of dart throwing skill was performed. In the first phase, the cognitive pretest was performed and the subjects were divided into two homogenies groups (each group 20 subjects): cognitive practice and no cognitive practice based on their age and pretest scores. The cognitive group received 8 sessions (45 minutes per session) of cognitive empowerment practice. Then, both groups received cognitive posttest. The cognitive tests were performed using Corsiblack (working memory) software. In the second phase of the study, each of the first phase groups were divided into 2 groups (10 subjects each group): observational + physical and physical. After dart throwing pretest, dart throwing was practiced in the form of observational and physical (3 sections of 20 throwing). The observational + physical group watched the skilled model of dart throwing through video in addition to dart throwing. Then, posttest was performed at the end of the second phase. Analysis of variance with repeated measures of 2 * 3 and 4 * 2 was used. The results showed that the working memory of cognitive group was significantly better than non-cognitive group. The cognitive + observational + physical group performed significantly better in the dart posttest than the other groups. It seems that cognitive empowerment can facilitate learning trough observation.